Anthropometric study and physical fitness in young tennis players—a systematic review - Luna-Villouta, Pablo Felipe (2022)
The objective of the study was to examine original scientific articles available in data bases for the past twenty-one years (2000-2021) concerning monitoring of anthropometry and physical fitness in young tennis players. A systematic review was carried out in three online data bases (PubMed, LILACS and Web of Science) from January, 2000 to May, 2021. Initially, 73 original articles were identified. After applying criteria of eligibility and exclusion, together with the procedure presented in the PRISMA flowchart, 14 articles were selected and were qualitatively analyzed. The results show the need for further research, mainly in South America and among women. However, it is important to point out that these studies offer anthropometric references very similar to those found in other regions in the world. On the other hand, anthropometry and performance in physical fitness tests show better indicators concerning chronological age, performance in a given modality (national ranking) and specific training. When genders were compared, significant differences were found in terms of anthropometry and physical fitness. Finally, both in women and in men, advanced maturity is associated with better performance in speed tests for movement, strength and muscle power. These data need to be considered in order to improve sports performance, detect talent and prevent injuries in adolescent tennis players.